2006
DOI: 10.1074/jbc.m513406200
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of the KLF2 Transcription Factor by Fluid Shear Stress Requires Nucleolin

Abstract: We have previously characterized the regulation of the KLF2 transcription factor gene by describing an induction complex that binds to and regulates its promoter. In the present study, by using DNA affinity chromatography and mass spectrometry, we have identified nucleolin as an additional protein that binds to a palindromic response region in the KLF2 promoter. The presence of nucleolin on the KLF2 promoter in macrophages was verified by electrophoretic mobility shift assays. Interestingly, in mouse and human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 57 publications
3
30
0
Order By: Relevance
“…28 Nucleolin has also been shown to be necessary for increased expression of Kruppel-like factor 2 in response to shear stress. 29 We have confirmed EC expression of nucleolin in human and murine tissues, with a staining pattern consistent with surface localization. Likewise, calreticulin, despite the lack of a classic secretion peptide or transmembrane domain, is present in human plasma, extracellular matrix, and body fluids, and may be found at increased concentrations in inflammatory disorders such as rheumatoid arthritis.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…28 Nucleolin has also been shown to be necessary for increased expression of Kruppel-like factor 2 in response to shear stress. 29 We have confirmed EC expression of nucleolin in human and murine tissues, with a staining pattern consistent with surface localization. Likewise, calreticulin, despite the lack of a classic secretion peptide or transmembrane domain, is present in human plasma, extracellular matrix, and body fluids, and may be found at increased concentrations in inflammatory disorders such as rheumatoid arthritis.…”
Section: Discussionsupporting
confidence: 58%
“…Given the known roles of calreticulin and nucleolin in EC function and signaling, [27][28][29][30][31] we further examined interactions among annexin A2, TLR4, calreticulin, and nucleolin using immunoprecipitation. Cell extracts prepared from unstimulated ECs or cells incubated with ␀ 2 GPI and anti-␀ 2 GPI Abs were subjected to immunoprecipitation using Abs against annexin A2, TLR4, or nucleolin.…”
Section: Annexin A2 Associates With Other Ec-surface Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our present study showed that the reduction of MK mRNA level because of the suppression of nucleolin transcription by the application of nucleolin antisense probe was about 50%. This phenomenon seems to be caused by following several reasons as follows: 1) transcriptional reduction of nucleolin was not complete even by the antisense probe application, probably because the nucleolin was a ubiquitously expressed gene in cells; 2) it is unknown whether the transcriptional regulation of MK by nucleolin is direct or indirect, and there may be another transcriptional pathway for the MK expression besides nucleolin (39,40); 3) translational disturbance of nucleolin induced by adding antisense probe may influence the stabilization of MK mRNA as shown in previous reports (41,42). It therefore seems important to disclose the molecular interaction between nucleolin and MK in the cellular biology of tooth germ development.…”
Section: Discussionmentioning
confidence: 99%
“…52 The transcriptional regulation is mediated by transcription factors, including AP-1, NF-ÎșB, Egr-1, SP-1, GATA 6, and Kruppel-like factor 2 (KLF2), each of which binds to its consensus motif in the gene promoter. [53][54][55][56][57][58] The posttranscriptional regulation is mediated by RNA-binding proteins that bind to mRNA and control its degradation rate. We have shown that the expression of genes encoding GM-CSF and urokinase-type plasminogen activator (uPA) is upregulated by shear stress through mRNA stabilization.…”
Section: Gene Expressionmentioning
confidence: 99%